A case of lichen planus pigmentosus in blaschkoid pattern in a 10-year-old female - Tulika Rai; Ayushi Bohara; Prasanna Kumar Jha (Wolters Kluwer Medknow Publications, 2021)
We describe a rare case of lichen planus pigmentosus (LPP) involving a 10-year-old female child with the involvement of the anterolateral aspect of the left thigh following the lines of Blaschko. LPP is a rare pigmented variant of lichen planus. Lines of Blaschko are lines of normal cell development. Histopathology showed melanophages in the papillary dermis with perivascular lymphocytic infiltrate and focal vacuolar change in basal layer consistent with a diagnosis of LPP.